Economic Insights into Workforce Dynamics: Analyzing Labor Supply, Demand, and Compensation - Aji, A. Sugeng Sapta; Akbardin, Muhammad (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
The research aims to comprehensively explore the multifaceted dynamics of the labor market, focusing on labor supply, demand, and compensation, and their implications for policy and future research. Employing a literature review approach, this study synthesizes insights from various disciplines, including economics, sociology, psychology, and public policy. Methodologically, it entails a systematic analysis of scholarly articles, empirical studies, and theoretical frameworks to elucidate the complex interplay of factors shaping workforce behavior and labor market outcomes. The findings reveal the intricate relationships between demographic characteristics, educational attainment, social norms, economic conditions, and technological advancements in influencing labor supply, demand, and compensation dynamics. Key insights include the significance of lifelong learning initiatives, the role of labor market institutions in ensuring fair compensation practices, and the importance of job quality enhancement measures in fostering workforce satisfaction and productivity. The research underscores the need for interdisciplinary approaches, longitudinal studies, and comparative analyses to address emerging challenges in the labor market and inform evidence-based policy interventions.